Patent for a foldable safety helmet. A development inspired by the maker culture - Caballero Rugel, Victor (2022)
This study presents the development and patenting of a foldable safety helmet based on a process created and inspired by the maker culture. Through four sequential phases —and the combination of inventive strategies— the process is presented and validated by obtaining the patent n.o 000829-2020/DIN-INDECOPI in September 2020. The transfer level of the methodology followed constitutes a contribution to any inventive development.